The comb sign in a patient with Crohn's disease. (2nd October 2021) - Ueda, Yoshitaka; Yanagi, Hidetaka
Abstract : There are many CT findings suggestive of Crohn's disease. The comb sign is one of them, and the sign helps us to diagnose it.